Efectos de los aceites esenciales de Eucalyptus globulus y de Mentha x piperita sobre áfidos de alfalfa - Bizet Turovsky, J. A. (Universidad Nacional del Litoral, 2022)
Although the use of synthetic insecticides is really advantageous for the control of agricultural pests at short periods, their continuous use can generate several longterm problems. This situation leads to a permanent search for alternative methods of control. In this paper were assessed the insecticidal activity and the effect on the reproduction of essential oils of Eucalyptus globulus and Mentha x piperita on aphids pest of alfalfa. The insecticidal activity of both essential oils was evaluated through two methods: toxicity by inmersion using the FAO dip test protocol and exposition to a treated leaf. Both essential oils produced toxicity by inmersion and by contact. The sublethal effect of essential oils on reproduction was evaluated using the leaf-dipping method. Both essential oils decreased progeny production of aphids species evaluated.